The stellar mass distribution of the Milky Way’s bar: an analytical model - Sormani, Mattia C.; Gerhard, Ortwin; Portail, Matthieu; Vasiliev, Eugene; Clarke, Jonathan (Monthly notices of the Royal Astronomical Society. Letters, 2022)
We present an analytic model of the stellar mass distribution of the Milky Way bar. The model is obtained by fitting a multicomponent parametric density distribution to a made-to-measure N-body model of Portail et al., constructed to match a variety of density and kinematics observational data. The analytic model reproduces in detail the 3D density distribution of the N-body bar including the X-shape. The model and the gravitational potential it generates are available as part of the software package agama for galactic dynamics, and can be readily used for orbit integrations, hydrodynamical simulations, or other applications.